공군기지의 C-UAS 센서 배치를 위한 다목적 최적화 모델 - 신민철; 최선주; 박종호; 오상윤; 정찬기 (한국군사과학기술학회지, 2022)
Recently, there are an increased the number of reports on the misuse or malicious use of an UAS. Thus, many researchers are studying on defense schemes for UAS by developing or improving C-UAS sensor technology. However, the wrong placement of sensors may lead to a defense failure since the proper placement of sensors is critical for UAS defense. In this study, a multi-object optimization model for C-UAS sensor placement in an air base is proposed. To address the issue, we define two objective functions: the intersection ratio of interested area and the minimum detection range and try to find the optimized placement of sensors that maximizes the two functions. C-UAS placement model is designed using a NSGA-II algorithm, and through experiments and analyses the possibility of its optimization is verified.
Keywords: C-UAS; Sensor Placement; Multi-objective Optimization; NSGA-Ⅱ; 무인항공기 대응 체계; 센서 배치; 다목적 최적화; 비지배 정렬 유전 알고리즘